Peran Kompetensi terhadap Perencanaan Sumber Daya Manusia - Samsudin, Acep; Prabowo, Budi; Bany, Maulyna Nur; Salma, Fatiha; Sandhy, Bella Karunia; Khumaira, Made Ayu Alivy (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This research aims to analyze the role of competence in human resource planning. The research method used in this journal is a literature review based on 5 international journals which discuss the role of competence between employees in human resource planning. The results of this research show that competency has long been a top priority, but is a serious challenge for organizations and human resource planning. In the current era of globalization and technology, competition is becoming increasingly fierce in terms of product quality, price, service, delivery, and so on. Therefore, businesses need to acquire knowledge and skills faster than competitors in order to stand out and thrive. Human resources, with the necessary knowledge and skills, are the main mechanism that allows any type of business to gain a competitive advantage and influence its overall performance.